Hip Fracture Surgery Between 24–48 Hours Is a Risk Factor for One-Year Mortality in Elderly Patients - Thamviriyarak, Pumsak (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: This study compared one-year survival rates between elderly patients who underwent hip fracture surgery within 24 hours versus those between 24–48 hours, and assessed factors influencing survival. Methods: This retrospective cohort study included elderly patients who underwent hip fracture surgery at Yasothon Hospital between June 1, 2019, and January 31, 2023. Patients were followed up until their final life status, as determined on January 31, 2024. In total, 212 patients were included, with 106 each undergoing surgery within 24 hours and between 24–48 hours. Statistical analyses were performed using the log-rank test and Cox regression. Results: A total of 36 patients (16.98%) died during the one-year follow-up period, with most deaths occurring in the 24–48-hour surgery group (27 patients, 25.47%). The mortality rates at 3 months, 6 months, and 1 year were 5.19%, 3.30%, and 8.49%, respectively. Significant mortality predictors included: age (adjusted HR = 1.06, 95% CI = 1.01–1.12); ASA class 3 (adjusted HR = 8.17, 95% CI = 1.03–64.79); general anesthesia (adjusted HR = 3.10, 95% CI = 1.46–6.57); complications (adjusted HR = 2.16, 95% CI = 1.02–4.56); and surgery performed after 24 hours (adjusted HR = 3.88, 95% CI = 1.67–9.02). Conclusions: Hip fracture surgery performed after 24 hours significantly increases the mortality risk in elderly patients. General anesthesia and postoperative complications are the key factors affecting survival. These findings emphasize the importance of surgery within 24 hours to reduce both mortality and complications in elderly patients.